Evaluation of Bone Mineral Density in Children with Acute Lymphoblastic Leukemia (ALL) and Non-Hodgkin's Lymphoma (NHL): Chemotherapy with/without Radiotherapy - Ali Ghassemi; Abdollah Banihashem; Nosrate Ghaemi; Saghi Elmi; Reza Erfani Sayyar; Sam Elmi; Habibollah Esmaeili (International Journal of Hematology-Oncology and Stem Cell Research, 2016)
Introduction: Acute lymphoblastic leukemia (ALL) and non-Hodgkin's lymphoma (NHL) are the most common malignancies in children and adolescents. Therapies such as corticosteroids, cytotoxic and radiotherapy will have harmful effect on bone mineral density (BMD) which can lead to increased possibility of osteoporosis and pathological fractures. Subjects and methods: This 3-year cross-sectional study was performed in 50 children with ALL (n=25) and NHL (n=25) at Dr. Sheikh Children's Hospital in Mashhad. Half the patients received chemotherapy alone, while the other half received chemotherapy plus radiotherapy (n=25). We assessed them in the remission phase by DEXA bone mineral densitometry at the lumbar spine and femoral neck (hip). The survey results were adjusted in accordance with age, height, sex and Body Mass Index. Results: The mean age was 8.28 ± 3.93 years. There was no significant difference in bone biomarkers (Ca, P, ALP, PTH) among ALL, NHL and also the two treatment groups. Children with ALL had lower density at the hip and lumbar spine (p-value<0.001 and p value=0.018, respectively). Among the total of 50 patients, 3 patients had normal results for detected hip BMD (6%), while 14 (28%) had osteopenia and 33 had osteoporosis (66%). Only one patient had normal BMD among all the patients who received chemotherapy plus radiotherapy, whereas 2 patients had normal BMD with just chemotherapy treatment. Conclusion: Given that 94% of our patients had abnormal bone density, it seems to be crucial to pay more attention to the metabolic status and BMD in children with cancer.